The effectiveness of educational media in preventing anemia among adolescent girls - Fitraniar, Iin; Anita, Anita; Yusnaini, Yusnaini (Science Midwifery, 2025)
Anemia is a prevalent health issue among adolescent girls, particularly in developing countries, with serious consequences for growth, cognitive function, and overall well-being. As this group undergoes critical physical development and prepares for future reproductive health, effective prevention strategies are essential. Health education has been widely recognized as a key intervention to improve awareness, knowledge, and behavioral changes related to iron intake and nutrition. This study systematically reviews 18 eligible articles published between 2013 and 2024 that examine the effectiveness of various educational media in preventing anemia among adolescent girls. A comprehensive literature search was conducted using Google Scholar and PubMed with relevant keywords in both English and Bahasa Indonesia. The included studies utilize different methodologies, such as quasi-experimental designs, participatory action research (PAR), and media development. Various educational media were analyzed, including leaflets, posters, videos, mobile applications, and interactive tools like educational games. The findings consistently demonstrate that educational interventions, particularly those utilizing digital and interactive media, effectively enhance knowledge, foster positive attitudes, and promote healthier behaviors. Approaches that actively involve participants, such as PAR, further improve engagement and personal responsibility for health. To maximize effectiveness, future programs should expand the use of digital platforms, such as social media and gamified learning tools, which have been shown to sustain attention and motivation. Additionally, integrating culturally relevant and community-based educational strategies can further enhance the long-term impact of anemia prevention efforts among adolescent girls.